Pemberdayaan Kampung Labanan Jaya Melalui Pendidikan Pengajaran, Digitalisasi Data, dan Agrowisata - Puji Astutik, Yuli; Ahmadong, Ahmadong; Dermawan, Zikri Setia; Inayah, Nur; Zakariah, Miftahul Hidayah; Andriani, Puspa Sari; Andriani, Desi Fatimah; Rita, Rita; Dewi, Dewi; Alifiansyah, Fikri (MAYARA: Jurnal Pengabdian Masyarakat, 2024)
Optimizing the empowerment of Labanan Jaya village, KKN students of Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tanjung Redeb (henceforth STITM Tanjung Redeb) carry out community service to provide experiences including science, technology, art, and religion which are useful for providing direction to solve problems appropriately. In terms of economic potential, the leading sectors of Labanan Jaya village are still dominated by agriculture, trade, and plantations. Using an analysis and observation approach in the field, it is known that Labanan Jaya village has many agrotourism sites where each RT has at least 1 agro-tourism site called Dasawisma. There is even one of the Dasawisma who was able to win an award at the provincial level. Therefore, training in digital marketing was carried out to provide material related to the use of the Canva application which is very useful for society in promoting their production. Besides, KKN students of STITM Tanjung Redeb also carry out a program in education, including teaching students of kindergarten, elementary/MI, and high school/MA in Labanan Jaya village. There are also additional programs provided, namely teaching TPA children to read the Al-Qur'an and additional lessons such as Fiqh and Aqidah Akhlak.